Evaluation of a parabolic trough collector performance - Kalogirou, Soteris A.; Panayiotou, Gregoris (My University, 2012)
In this paper the collector erected at the Archimedes Solar Energy Laboratory is initially presented followed by the performance evaluation of the collector. The collector is made by Nep Solar from Australia. It has an aperture area of 14.4 m2, a concentration ratio of 13.7 and can be operated up to 200°C. The collector aperture is 1208 mm and the receiver pipe is stainless steel 304 L with a diameter of 28mm, coated with selective coating having an absorptance of 0.93 and an emitance of 0.18. The collector is orientated with its axis in the East-West direction. The advantages of this tracking mode are that very little collector adjustment is required during the day and the full aperture always faces the sun at noon. A dedicated computer-operated tracking system is responsible for keeping the collector focused at all times. The collector is connected to a hot water storage tank which has a capacity of 300 liters. The collector fluid used in the tests is water, which is pressurized to avoid boiling in the receiver. The performance obtained is very satisfactory and agrees with the performance curve given by the manufacturer
Keywords: Renewable energy resources; Mathematical models